2010
DOI: 10.1134/s1070428010070031
|View full text |Cite
|
Sign up to set email alerts
|

Some condensations of methyl 4-acetylphenylcarbamate

Abstract: Condensation of methyl 4-acetylphenylcarbamate with isatin in the presence of diethylamine afforded methyl 4-[(3-hydroxy-2-oxo-2,3-dihydro-1H-indol-3-yl)acetyl]phenylcarbamate which was converted into the corresponding chalcone on heating in glacial acetic acid in the presence of hydrochloric acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…We also found that three-component reactions of N -benzylbenzimidazolium salts, isatins and malononitrile or ethyl cyanoacetate gave a series of the novel zwitterionic salts and the unexpected products with opening of the imidazole ring58. These results together with the previously reports596061626364 indicated that the 1,3-dipolar cycloaddition reactions of cyclic nitrogen N -ylides with 3-methyleneoxindoles have fruitful chemistry. Due to the spirooxindole existing in a large number of naturally occurring and medicinally relevant substances, the development of efficient method for constructing the spirooxindole motif is of great importance in synthetic organic and medicinal chemistry6566676869707172.…”
supporting
confidence: 69%
“…We also found that three-component reactions of N -benzylbenzimidazolium salts, isatins and malononitrile or ethyl cyanoacetate gave a series of the novel zwitterionic salts and the unexpected products with opening of the imidazole ring58. These results together with the previously reports596061626364 indicated that the 1,3-dipolar cycloaddition reactions of cyclic nitrogen N -ylides with 3-methyleneoxindoles have fruitful chemistry. Due to the spirooxindole existing in a large number of naturally occurring and medicinally relevant substances, the development of efficient method for constructing the spirooxindole motif is of great importance in synthetic organic and medicinal chemistry6566676869707172.…”
supporting
confidence: 69%
“…Heating of compound 118 with hydrazine in ethanol gave an indolone‐pyrazole spiro‐fused heterocycle 123 ( Scheme 31). [190] Heterocycle 118 [191] also interacts with 3‐aminocrotonic acid ethyl ester, acetoacetic ester, but in this case spirocyclic compounds are not formed [192] . Analogs of compound 122 with benzyl and ethoxycarbonyl groups at indole and pyrazole nitrogen atoms, respectively, can also be obtained by reacting 3‐ethoxymethylidene, 3‐benzyloxycarbonylmethylidene, 3‐cyanomethylidene or 3‐benzylideneindoles with diethyl azodicarboxylate (EtO 2 CN=NCO 2 Et) in the presence of an equimolar amount of PPh 3 at room temperature with yields of 56–99 % [193] .…”
Section: Syntheses Of Spiroheterocycles From 3‐alkylidene‐indol‐2‐onementioning
confidence: 99%
“…Heteroaromatic N-ylides such as pyridinium, thiazolium, quinolinium, isoquinolinium methylides which are readily available from the alkylation of azaaromatic heterocycles and sequential deprotonation reaction have also been used as one kind of reactive azomethine ylides extensively in cycloadditions for the synthesis of the fused heterocycles with a nitrogen at the point of fusion. 12 Our group had reported the green synthetic methods for complex heterocyclic compounds, such as efficient synthesis of spiro[indoline-3,1′-pyrrolo[2,1- a ]isoquinolines via 1,3-cycloaddition reactions of 3-phenacylideneoxindoles with aza-aromatic N-ylides generated from isoquinolinium salts. 13 Wang's group synthesized some analogues by using 3,4-dihydroisoquinolinium salts.…”
Section: Introductionmentioning
confidence: 99%